2010
DOI: 10.1203/pdr.0b013e3181f2e81c
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen is neuroprotective and preserves cerebrovascular reactivity in asphyxiated newborn pigs

Abstract: Hydrogen (H 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 35 publications
4
31
1
1
Order By: Relevance
“…Experimental evidence from hypoxiaischaemia in pigs have shown a neuroprotective effect of topiramate, an anticonvulsant that may reduce excitotoxicity and calcium overload 208 , and of nicotine, which has antiapoptotic features and attenuates the post-hypoxic decrease in Brain-derived neurotrophic factor 209,210 . Finally, recent evidence from newborn pigs suggests a neuroprotective effect of reoxygenation with room-air supplemented with 2.1% hydrogen 211 .…”
Section: Combination With Pharmacological Agentsmentioning
confidence: 96%
“…Experimental evidence from hypoxiaischaemia in pigs have shown a neuroprotective effect of topiramate, an anticonvulsant that may reduce excitotoxicity and calcium overload 208 , and of nicotine, which has antiapoptotic features and attenuates the post-hypoxic decrease in Brain-derived neurotrophic factor 209,210 . Finally, recent evidence from newborn pigs suggests a neuroprotective effect of reoxygenation with room-air supplemented with 2.1% hydrogen 211 .…”
Section: Combination With Pharmacological Agentsmentioning
confidence: 96%
“…In our study made on acute changes after birth asphyxia, asphyxia was shown to significantly increase the number of damaged neurons after 4 hours, moreover, hydrogen ventilation was shown to partially alleviate the hypoxic/ischemic neuronal damage [141]. However, we could not show statistically significant increases of COX-2 immunopositive neurons, perhaps there was a slight tendency for increased number of positive neurons after asphyxia in the parietal and occipital cortices.…”
Section: Map-2 Densitycontrasting
confidence: 66%
“…Indeed, the magnitude of pial arteriolar diameter changes in response to these stimuli was virtually identical to those determined in the acute model of brain asphyxia [65,69,141].…”
Section: Map-2 Densitysupporting
confidence: 65%
See 1 more Smart Citation
“…Accordingly, various antioxidant approaches have been shown to prevent the acute attenuation of CR in the piglet. Recently, molecular hydrogen (H 2 ) - a putative selective inhibitor of hydroxyl radicals [11] - was found to prevent acute post-asphyxic CR impairment with a concomitant neuroprotective effect in piglets [12]. …”
Section: Introductionmentioning
confidence: 99%